Plant design for the production of ethyl alcohol from wood wastes - David, Renato M. (College of Engineering, 1975)
A plant to produce ethanol from wood waste has been designed to produce 560,000 gallons of 95 percent ethyl alochol. The plant is proposed to be constructed in Wakas, Bocaue, Bulacan because of the proximity of the place to the various sawmills from which the woodwaste would be obtained. In addition, the place is near the Marilao River where the treated waste could be channeled. Furthermore, the place is not very far from Greater Manila area where major consuming industries are located. The total investment requirement for the proposed plant is P15,609,000 broken down as follows : P13, 267,380 for fixed capital investment and P2,342,000 for the working capital. From the economic point of view, the venture presents a promising picture. The rate of return is 25 percent and the pay-off period is 2.5 years.